Acute pancreatitis associated with duodenal obstruction induced by groove pancreatitis: A case report. Issue 22 (4th June 2021) - Li, Jiayan; Liu, Qianyi; Liu, Zhishang; Cen, Chuan; Yang, Yuyu; Ye, Jianming; Xu, Li; Lu, Xiji; Chen, Dongfeng; Ruan, Weishan
Abstract: Rationale: Groove pancreatitis (GP) is a rare form of chronic pancreatitis. Since GP presents with nonspecific symptoms, it can be challenging to diagnose. Duodenal obstruction is often caused by malignant diseases; however, when associated with acute pancreatitis, it is rarely induced by groove pancreatitis. Patient's concerns: A 56-year-old man who presented with acute pancreatitis complained of recurrent upper abdominal discomfort. His concomitant symptoms included abdominal pain, postprandial nausea, and vomiting. Contrast-enhanced computed tomography (CT) of the abdomen showed thickening of the duodenum wall. Gastrointestinal radiographs and upper gastrointestinal endoscopy showed an obstruction of the descending duodenum. Diagnosis: The pathologic diagnosis was groove pancreatitis. Interventions: The patient underwent gastrojejunostomy to relieve the obstruction. Outcomes: The patient had an uneventful recovery with no complications. Lessons: Groove pancreatitis should be considered in the differential diagnosis of patients presenting with acute pancreatitis and duodenal obstruction. These data can help to make a precise diagnosis and develop an appropriate treatment plan.